2018
DOI: 10.3390/ijms19103069
|View full text |Cite
|
Sign up to set email alerts
|

Her2-Targeted Therapy Induces Autophagy in Esophageal Adenocarcinoma Cells

Abstract: Esophageal adenocarcinoma (EAC) is a highly lethal cancer type with an overall poor survival rate. Twenty to thirty percent of EAC overexpress the human epidermal growth factor receptor 2 (Her2), a transmembrane receptor tyrosine kinase promoting cell growth and proliferation. Patients with Her2 overexpressing breast and gastroesophageal cancer may benefit from Her2 inhibitors. Therapy resistance, however, is well documented. Since autophagy, a lysosome-dependent catabolic process, is implicated in cancer resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Cardiomyocyte apoptosis induced by autophagy flux block is a relatively newly discovered signal transduction pathway (Feng et al, 2018). The expression of LC3II and P62 were increased after AngII treatment in the cardiomyocytes, and cardiomyocytes apoptosis was increased as well, indicating an increase in the production of autophagy and blockage in the autophagic flow with AngII (Janser et al, 2018). In this study, it was found that irisin In conclusion, irisin may reduce myocardial apoptosis by increasing autophagy activity and autophagy flux, and inhibiting the apoptosis signaling factor in myocardial cells damaged by AngII.…”
mentioning
confidence: 99%
“…Cardiomyocyte apoptosis induced by autophagy flux block is a relatively newly discovered signal transduction pathway (Feng et al, 2018). The expression of LC3II and P62 were increased after AngII treatment in the cardiomyocytes, and cardiomyocytes apoptosis was increased as well, indicating an increase in the production of autophagy and blockage in the autophagic flow with AngII (Janser et al, 2018). In this study, it was found that irisin In conclusion, irisin may reduce myocardial apoptosis by increasing autophagy activity and autophagy flux, and inhibiting the apoptosis signaling factor in myocardial cells damaged by AngII.…”
mentioning
confidence: 99%
“…Therefore, there is a lot of interest in using this type of samples for pre-clinical studies. The ATG proteins MAP1LC3B, p62/SQSMT1, Beclin-1 and LAMP2A are frequently stained and used to assess the status of autophagy [52,[147][148][149][150][151][152][153]. These proteins are unfortunately not specific to autophagy and therefore interpretation of autophagic activity based on ATG protein levels is still under discussion.…”
Section: Current Autophagy Markers and Their Limitationsmentioning
confidence: 99%
“…Therefore, it's imperative to identify innovative methods and biomarkers for early stage detection along with new treatment strategies. Cumulative evidences showed that autophagy was involved in the pathogenesis of EAC and may provide bene ts for patients [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the autophagy in the EAC has not been studied thoroughly, alterations in autophagy have been identi ed in several studies [11][12][13] . In addition, the autophagy-related genes (ARGs) and proteins including Beclin-1 and p62 have been already studied in EAC [8,10,14] . These studies demonstrated the critical roles of autophagy in the development of EAC and responses to therapy.…”
Section: Introductionmentioning
confidence: 99%